EFEKTIVITAS PENERAPAN MEDIA THINK STACK ECONOMY DENGAN MODEL PEMBELAJARAN KONTEKSTUAL DALAM MENINGKATKAN PEMAHAMAN KONTEKSTUAL SISWA - Khomsatun Nikmatul Husna; Nur Anita Yunikawati (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2026)
This study aims to examine the effectiveness of implementing the Think Stack Economy media combined with a contextual teaching and learning model in improving students’ contextual understanding of the topic of Banking and Non-Banking Financial Institutions. This research employed a quantitative approach with a quasi-experimental design, involving an experimental class and a control class at a public senior high school in Kepanjen. Data were collected through written tests in the form of pretests and posttests, then analyzed using the N-Gain test, normality test, Mann-Whitney U test, and Cohen’s d test. The findings reveal that the experimental class, which implemented the Think Stack Economy media with the contextual learning model, achieved a substantially higher improvement in contextual understanding than the control class, with a large effectiveness category. These findings confirm that combining game-based media with a contextual learning model offers an effective and innovative alternative strategy for economics instruction.